ANALISIS KETENAGAKERJAAN MAHASISWA SISTEM INFORMASI ANGKATAN 2023(STUDI KASUS: PEKERJAAN ORANG TUA MAHASISWA) - tri wahyuni, tri wahyuni; Nurnita, Nurnita; Khairul Khatimah, Khairul Khatimah; Yesti Andini, Yesti Andini; Muhammad Suratman, Muhammad Suratman; Muhammad Bintang Juliawan, Muhammad Bintang Juliawan; Achmad Isya Alfassa , Achmad Isya Alfassa (TEKNOFILE : Jurnal Sistem Informasi, 2024)
This study analyzes the parental employment of Information Systems students class of 2023 at a higher education institution in Indonesia. With a sample of 63 students, this study aims to identify and describe the types of parental employment and examine the dominant occupations overall and in each class. The data collection method used an online survey distributed to each class. The results showed that the most dominant occupation was farmer (42.2%), followed by trader (20.3%), civil servant (15.6%), entrepreneur (10.9%), and other occupations (10.9%). Analysis by class revealed that farmers were consistently the dominant occupation in all classes, with the highest number in class A (10 people), followed by class C (9 people), and class B (8 people). These findings provide important insights into the socio-economic background of Information Systems students and can contribute to the development of more responsive educational policies. This study also emphasizes the importance of the agricultural sector in the context of students' parents' occupation, which may affect students' career orientation and academic achievement in the future.